Captain Underpants and the sensational saga of Sir Stinks-A-Lot - Pilkey, Dav; Garibaldi, Jose; Dzioba, Wes (London : Scholastic, 2022)
George and Harold, and their doubles, Yesterday George and Yesterday Harold, have a good thing going. Two of them go to school, while the other two hide in the tree house playing video games - then they switch! But when gym teacher Mr. Meaner uses mind-control to create obedient, perfect robot children, the future of humanity is in their hands.
Keywords: Captain Underpants -- (fiktiivinen hahmo); George -- (fiktiivinen hahmo); Harold -- (fiktiivinen hahmo); kepposet; koulunkäynti; alakoulu; projektit; muutos; koululaiset; liikunnanopettajat; kaksoisolennot; supersankarit; lastenkirjallisuus; koululaisromaanit; poikakirjat; huumori; romaanit; kaunokirjallisuus; englanninkielinen kirjallisuus